Representasi Gerakan Politik Perempuan dalam News Journalism (Analisis Teks Berita Koran Lama Tentang Gerwani PKI dan Pemilu 2014) - Citra Orwella (LP2M IAIN Tulungagung, 2017)
The text construction in newspapers and online medias are both of them are the mass media communications. The newspaper cacths up daily realtiy in everyday life. One of the realities that are often raised and shown by those media, newspapers and online media are about feminism. Feminism is quite influencing on popular culture. This can be known from the many products of popular culture (such as using language text on news, for example) with feminism theme. This study wants to find out how the construction of feminism in Indonesin news (newspaper and online medias) and then compared between the news text consruction in 1960-an and nowdays.This study is a qualitative description using critical discourse analysis method by adopting the Sara Mills model’s. By performing its analysis obtained that there is a scheme in the text, namely the micro level and macro level. From all of these aspects can be known how the text of print and online media construct feminism to citizen’s mind. Keywords: news, journalism,critical discourse analysis, feminism, Sara Mills.